Трипільські протоміста - Шмаглій, М.М.; Відейко, М.Ю. (Археологія, 1993)
Робота присвячена важливій науковій проблемі — структурно-функціональному аналізу призначення поселень-гігантів Трипільської культури. Автори намагаються визначити їх як протоміста. Введение в научный оборот результатов исследований крупных трипольских поселений является важной задачей. На примере этих памятников мы можем наблюдать начальные процессы урбанизации — превращения поселений ранних земледельцев в поселения протогородского типа. На территории, занятой трипольскими племенами, эти процессы протекали до середины IV тыс. до н. э. синхронно с развитием протогородской цивилизации на Древнем Востоке. Таким образом, Юго-Восточная Европа может быть включена в число районов формирования древних городских цивилизаций медного века. Крупные трипольские поселения, насчитывавшие до 10—14 тыс. населения, были интегративными экономическими, общественными, военными и культовыми центрами, образуя сложные структуры типа древневосточных «номов» с целью контроля над окружающей территорией. Здесь получили развитие монументальная архитектура — оборонительные сооружения и общественные постройки, начался процесс зарождения систем письменности. Все это делает актуальным дальнейшее изучение крупных трипольских поселений-протогородов. The bringing into scientific circulation the results of the invastigation of the large-scale Tripolian settlements is an important task. By example of these memorials we can observe the initial processes of urbanization — the transformation of the early-farmer’s settlements into the settlements of the protocity type. At the territory occupied by Tripolian tribes these processes proceeded until the middle of the 4th millenium B. C. synchronously to the development of proto-city zivilisation at Ancient East. Thus South-East Europe could be included into the number of the regions where the ancient urban zivilisations of the Brazen Age were formed. The large-scale Tripolian settlements numbered up to 10—14 ths inhabitants were the integratetive economic, public, military and cult centers which formed the complex structures of Ancient-East «nomus»-type in order to control the surrounding territories. Here the monumental architecture — the fortifications and public buildings were developed and process of the origin of the writting systems was began. All this makes the subsequent study of the large-scale Tripolian settlements — proto-cities urgent.